Catchment Functioning Under Prolonged Drought Stress: Tracer‐Aided Ecohydrological Modeling in an Intensively Managed Agricultural Catchment. Issue 3 (25th March 2021) - Yang, Xiaoqiang; Tetzlaff, Doerthe; Soulsby, Chris; Smith, Aaron; Borchardt, Dietrich
Abstract: High spatial heterogeneity of catchment properties enhances the variability of ecohydrological responses to changing natural and anthropogenic conditions, like the European‐wide droughts in 2018–2019. Based on new adaptations of a tracer‐aided, process‐based ecohydrological model (EcH2 O‐iso), we investigated drought‐induced nonstationary ecohydrological behavior in a small agricultural headwater catchment (1.44 km 2 ) in central Germany. Multiple environmental time‐series helped inform various aspects of catchment functioning that have been impacted by agricultural activity and changing climate conditions and helped to further constrain model calibration. Multi‐criteria calibration showed that data collected during drought years were highly informative in reproducing the changes in stream water dynamics. Further, inclusion of δ 2 H and δ 18 O data was valuable for reducing model uncertainty and increasing confidence in simulations of green‐ and blue‐water flux partitioning and storage‐flux‐age interactions. Using the best‐performing calibrations, we further analyzed the high spatiotemporal variability of internal ecohydrological processes and the varying responses of fluxes and associated water ages to prolonged drought stress. Under drought conditions, modeled stream runoff contributed from deeper, older storages increased significantly after a particularly wet season, resulting in a sharp increase in stream water age. Unlike relatively minor changes in soil evaporation, seasonally typical transpiration fluxes were initially maintained in April–June but dramatically decreased as the drought further developed in July–September. Importantly, the tracer‐based transpired water age was much older after April, providing a potential indicator of drought impacts and the need for precautionary management responses. Our findings are important for similar agricultural headwater ecosystems in other drought‐sensitive regions. Key Points: Adapted tracer‐aided ecohydrological model (EcH2 O‐iso) captured catchment functioning impacted by agriculture and drought stress Inclusion of drought‐period data and isotope tracers in multi‐criteria calibrations improved representation of internal processes Drought‐induced responses differed for green and blue water dynamics, and flux water ages provided sensitive indicators of stress